2006
DOI: 10.1634/stemcells.2005-0457
|View full text |Cite
|
Sign up to set email alerts
|

Murine Embryonic Stem Cells Secrete Cytokines/Growth Modulators That Enhance Cell Survival/Anti-Apoptosis and Stimulate Colony Formation of Murine Hematopoietic Progenitor Cells

Abstract: STEM CELLS 2006;24: 850 -856

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 10 publications
2
50
1
Order By: Relevance
“…The theoretical predictions regarding removal of secreted factors were experimentally verified by collecting VEGF, which is known to be secreted by mESCs (27). We were indeed able to measure secreted VEGF (Fig.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The theoretical predictions regarding removal of secreted factors were experimentally verified by collecting VEGF, which is known to be secreted by mESCs (27). We were indeed able to measure secreted VEGF (Fig.…”
Section: Resultssupporting
confidence: 52%
“…Because the exit from the ESC state seen under perfusion is related to the presence of the intact ECM, it is possible that a removal of MMPs under perfusion is responsible. Indeed, MMPs are known to be secreted by mESCs (27), and we are able to recover MMP2 from perfused cells (Fig. 3H), illustrating that it is being removed by flow.…”
Section: Down-regulation Of Cell-secreted Signals Drives Escs Toward Anmentioning
confidence: 75%
“…Interestingly, compound mutant AT2 cells showed increased expression of SDF1a. This molecule is a regulator of progenitor cell recruitment, vascular cell differentiation, and angiogenesis (76)(77)(78), and has previously been shown to be suppressed by FGF signaling (79,80).…”
Section: Discussionmentioning
confidence: 99%
“…The 25% ESC-CM group showed a decrease in apoptotic cells and p21 protein expression. Furthermore, it was also reported that the cells cultured in 25% ESC-CM had enhanced HCEC proliferation and promoted HCECs into the cell cycle [26][27][28][29][30]. To summarize, in these studies, primary cultures of HCECs were cultured using 25% mouse embryonic stem cell-conditioned medium.…”
Section: Mouse Embryonic Stem Cell-conditioned Mediummentioning
confidence: 99%